Predicting heart failure during hospitalization in myocarditis. (3rd May 2023) - Rocha Carvalho, P; Carvalho, C; Bernardo, M; Moreira, I; Ferreira, C; Silveira, I; Fontes, P; Moreira, J I
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Currently, there is little evidence available regarding their predictive potential of Monocyte-to-lymphocyte ratio (MLR) in patients diagnosed with myocarditis. Purpose: We aimed to investigate if MLR can predict heart failure during hospitalization in patients with clinical suspicious of acute myocarditis. Methods: Retrospective study with patients admitted with the clinical suspicion of myocarditis in our center from February/2016 to September/2021. A total of 74 patients were included and divided into two groups based on MLR. ROC-analysis was conducted and AUC was calculated for the prediction of heart failure during hospitalization (0.82). Optimal cut-off for MLR was calculated by means of the Youden Index (MLR ≥ 0, 817 (sens.: 73%, spec.: 80%). The primary outcome was heart failure during hospitalization. Results: We included 74 patients (90, 5% males; mean age 37, 1±15, 1 years old), 96, 8% presenting with chest pain and 68, 9% presenting with ST-segment elevation on electrocardiogram. During hospitalization, 4 patients needed ionotropic support, 7 had supraventricular tachycardia, 14 non-sustained ventricular tachycardia, 2 sustained ventricular tachycardia, 1 needed extracorporeal membrane oxygenation and 11 had heart failure. Both groups had similar age (39, 0±16, 9 vs 36, 5±16, 7 years, p=0, 59), previous history of myocarditis (8, 9% vs 5, 6%, p=0, 65), smoking history (16, 7% vs 33, 9%, p=0, 34), diabetes mellitus (7, 1% vs 2, 6%, p=0, 24), dyslipidemia (33, 3% vs 19, 6%, p=0, 23), arterial hypertension (11, 1% vs 14, 3%, p=0, 73), ST-segment elevation on admission (72, 7% vs 63, 8%, p=0, 45), pro-BNP levels on admission [522 (IQR 222-1253) mg/dl vs 495 (IQR 222-970) mg/dl, p = 0, 46]. Patients with MLR ≥ 0, 817 (24, 3%) had lower Left ventricular ejection fraction on admission (45, 9%±14, 1% vs 53, 3%±8, 4, p=0, 008), high Peak C-reactive protein [13 (IQR 4, 5-22) vs 4, 5 (IQR 4-6, 1), p=0, 001] and peak troponin levels [1, 98 (IQR 0, 98-2, 81) vs 0, 87 (IQR 0, 55-1, 74), p=0, 007] were higher in this group. Throughout a median hospital stay of 4 days (IQR 3, 5–7), 11 patients (17, 7%) experienced the primary outcome. After adjusting for possible cofounders, MLR ≥ 0, 817 was an independent predictor of heart failure during hospitalization (HR 6, 83, 95% CI 1, 55-30, 01, p=0, 011). Conclusion: MLR in our population, was a predictive factor for heart failure during hospitalization in patients with acute myocarditis. MLR could facilitate an early risk stratification and clinical management in these patients.